The necessity of a herd health management programme for dairy goat farms in Malaysia - Shahudin, Muhammad Syafiq; Abdul Ghani, Ahmad Afifi; Saad, Mohd Zamri; Abu Bakar @ Zakaria, Md Zuki; Abdullah, Faez Firdaus Jesse; Haron, Abd Wahid; Abu Hassim, Hasliza (Universiti Putra Malaysia Press, 2018)
In Malaysia, an increasing number of new dairy goat farms are being opened by smallholders due to increasing demand for dairy goat products. However, most of the dairy goat farms are not managed well due to poor knowledge and information about the standard management of dairy goat. Indeed, low performance of dairy goats with respect to growth performance, feed utilisation, disease resistance and milk production has been associated with improper rearing protocol, specifically, herd health protocol. For this reason, implementation of a herd health management programme is important as a standard rearing management and disease control programme for dairy goat farms. A herd health management programme is a preventive programme intended to keep the herd healthy and free of disease through comprehensive husbandry management that includes nutrition management, breeding, parasite control, vaccination, biosecurity and environmental management with the goal of improving the herd's performance and productivity. However, the level of acceptance from farmers for implementing herd health management programmes varies, especially among smallholder farmers. Thus, veterinarians play an important role as advisor in transferring knowledge of the importance of herd health management to the farmers.